2018
DOI: 10.1080/15548627.2018.1474311
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic exon splicing function of TARDBP interacts with autophagy in nervous tissue

Abstract: ALS: amyotrophic lateral sclerosis; ATG4B: autophagy related 4B cysteine peptidase; AUC: area under the curve; FTLD: frontotemporal lobar degeneration; iPSC: induced pluripotent stem cells; ROC: receiver operating characteristic; TARDBP: TAR DNA binding protein; RT-qPCR: quantitative RT-PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…TARDBP knockout mice show embryonic lethality [68, 130] and partial knockdown of TDP-43 results in motor deficits [68, 165] and motor neuron loss in mice [165]. Several recent cell-based studies have reported that TDP-43 knockdown leads to incorporation of cryptic exons [58, 76, 140, 142], also detected in FTD/ALS patient cerebral cortical areas with substantial TDP-43 aggregation [76], in AD with TDP-43 proteinopathy [140], and in motor cortex, spinal cord, brainstem and occipital cortex from patients with ALS [146]. Incorporation of cryptic exons in neurons lacking nuclear TDP-43 may, in turn, reduce expression of essential proteins via nonsense-mediated decay of aberrant transcripts; this process is likely involved in both sporadic and C9orf72 -FTD/ALS.…”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%
See 1 more Smart Citation
“…TARDBP knockout mice show embryonic lethality [68, 130] and partial knockdown of TDP-43 results in motor deficits [68, 165] and motor neuron loss in mice [165]. Several recent cell-based studies have reported that TDP-43 knockdown leads to incorporation of cryptic exons [58, 76, 140, 142], also detected in FTD/ALS patient cerebral cortical areas with substantial TDP-43 aggregation [76], in AD with TDP-43 proteinopathy [140], and in motor cortex, spinal cord, brainstem and occipital cortex from patients with ALS [146]. Incorporation of cryptic exons in neurons lacking nuclear TDP-43 may, in turn, reduce expression of essential proteins via nonsense-mediated decay of aberrant transcripts; this process is likely involved in both sporadic and C9orf72 -FTD/ALS.…”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%
“…Incorporation of cryptic exons in neurons lacking nuclear TDP-43 may, in turn, reduce expression of essential proteins via nonsense-mediated decay of aberrant transcripts; this process is likely involved in both sporadic and C9orf72 -FTD/ALS. Indeed, a recent cell-based study found expression of cryptic exon-containing ATG4B mRNA, accompanied by reduced ATG4B protein, in the context of TARDBP knockdown [146]. “TDP-43 depletion,” the loss of TDP-43 from neuronal nuclei in the absence of a visible, well-developed cytoplasmic inclusion, is a recently described feature of C9orf72 -bvFTD [155] and sporadic ALS [10, 11], and may occur early in the disease process.…”
Section: Clinical and Anatomical Features Of C9orf72-ftd/alsmentioning
confidence: 99%
“…The involvement of TDP-43 was first reported in nuclear RNA transcription, mRNA stability regulation and modulation of mRNA splicing [9, 10, 12]. In addition, TDP-43’s role in a wide variety of cellular events, such as nucleocytoplasmic transport [51], mitochondrial stability [31], and autophagy pathways [6, 67], are beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, no previous evidence of its involvement in this disease were known, except with the fact that PKC levels were increased in ALS patients [29]. The involvement of the potential loss of PKCßII in ALS pathogenesis can be diverse, as this protein interacts with mitochondria [30], and with autophagic function [31], to name a few, and both elements are involved in ALS [32,33] Other changes in lipid components of nuclei include plasmalogens. These membrane glycerophospholipids contain a fatty alcohol with a vinyl-ether bond at the sn-1 position, and they are enriched in polyunsaturated fatty acids at the sn-2 position of the glycerol backbone.…”
Section: Discussionmentioning
confidence: 99%